Chromophore Orientation-Dependent Photophysical Properties of Pyrene–Naphthalimide Compact Electron Donor–Acceptor Dyads: Electron Transfer and Intersystem Crossing - Imran, Muhammad; Sukhanov, Andrey A; Maity, Partha; Elmali, Ayhan; Zhao, Jianzhang; Karatay, Ahmet; Mohammed, Omar F; Voronkova, Violeta K (The journal of physical chemistry. B, 2021)
In order to study the effect of mutual orientation of the chromophores in compact electron donor–acceptor dyads on the spin-orbit charge transfer intersystem crossing (SOCT-ISC), we prepared naphthalimide (NI)–pyrene (Py) compact electron donor–acceptor dyads, in which pyrene acts as an electron donor and NI is an electron acceptor. The connection of the two units is at the 4-C and 3-C positions of the NI unit and the 1-position of the pyrene moiety for dyads NI-Py-1 and NI-Py-2, respectively. A charge transfer absorption band was observed for both dyads in the UV–vis absorption spectra. Upon nanosecond pulsed laser excitation, long-lived triplet states (lifetime is 220 μs) were observed and the triplet state was confined to the pyrene moiety. The ISC efficiency is moderate to high in nonpolar to polar solvents (singlet oxygen quantum yield: ΦΔ = 14–52%). Ultrafast charge separation (ca. 0.81 ps) and charge recombination-induced ISC (∼3.0 ns) were observed by femtosecond transient absorption spectroscopy. Time-resolved electron paramagnetic resonance spectroscopy confirms the SOCT-ISC mechanism; interestingly, the observed electron spin polarization pattern of the triplet state is chromophore orientation-dependent; and the population rates of the triplet sublevels of NI-Py-1 (P x:P y:P z = 0.2:0.8:0) are drastically different from those of NI-Py-2 (P x:P y:P z = 0:0:1).